Sociabilidade e modernidade nos espaços de lazer da capital cearense do início do século XX (1901 a 1910) - Vieira, Carla Manuela da Silva (2012)
The practices of sociability and culture of a society is a rich field to understand the social relations between the individuals who constitute it. In this study, we get to investigate how these forms and practices were related to the idea and the desire for modernity of the city of Fortaleza, capital of Ceará in the early twentieth century (1901-1910), around the uses and pictures which were made of the leisure facilities of the city. This modernity was materialized in the remodeling and reorganization of the capital's public spaces, but also translated too by the search for modes of conduct and thought of elitist societies, European especially French major paradigm for the rest of the civilized world that it was intended and modern. In this process, the spaces of sociability and leisure appear as a privileged locus for the development of these modes and journalistic chronicle of the period, which recorded aspects of several orders, including those related to mundane sociability, shows up as research source on such matters It is this same chronicle that allows the evaluation of the uses and images that were of leisure facilities available to the city, important icons of modernity and civility to the elites of Fortaleza city dwellers, but also significant windows that exposed the deep contrasts between design of these groups and the reality of the popular classes, always identified with the colonial past and backward country that wanted to overcome